Oxidative stress contributes to hypermethylation of Histone H3 lysine 9 in placental trophoblasts from preeclamptic pregnancies - Gu, Yang; Cooper, Danielle; Lewis, David F.; Zoorob, Dani; Wang, Yuping (Frontiers in Endocrinology, 2024)
Background and objective Aberrant epigenetic regulation and increased oxidative stress in the placenta play a significant role in placental pathophysiology and fetal programming in preeclampsia, a hypertensive disorder in human pregnancy. The purpose of the study is to investigate if hypermethylation of histone H3K9 occurs in placental trophoblasts from preeclampsia. Methods Trophoblasts were isolated and cultured from 14 placentas, 7 from normotensive pregnant women and 7 from preeclamptic pregnancies. Methylated H3K9 expression and antioxidant superoxide dismutase expression were determined by Western blot. We also examined consequences of oxidative stress and the downstream effects of histone methyltransferase inhibition on H3K9 expression associated with antioxidant CuZn-SOD and Mn-SOD expression in placental trophoblasts. Results We found that expression of mono-, di-, and tri-methylation of histone H3 lysine 9 (H3K9me1, H3K9me2 and H3K9me3) was significantly increased, p<0.01, which correlated with downregulation of antioxidant superoxide dismutase CuZn-SOD and Mn-SOD expression, in trophoblasts from preeclamptic placentas compared to those from uncomplicated control placentas. We further demonstrated hypoxia could promote histone H3K9 methylation in placental trophoblasts, and hypoxia-induced upregulation of H3K9me1, H3K9me2 and H3K9me3 expression was reversible when hypoxic condition was removed. In addition, we also uncovered that inhibition of methyltransferase not only prevented hypoxia-induced upregulation of H3K9me1, H3K9me2 and H3K9me3 expression, but also abolished hypoxia-induced downregulation of CuZn-SOD and Mn-SOD expression in placental trophoblasts. Conclusions These findings are noteworthy and provide further evidence that increased oxidative stress in the intrauterine environment is likely a mechanism to induce aberrant histone modification in placental trophoblasts in preeclampsia. Moreover, CuZn-SOD and Mn-SOD expression/activity are possibly H3K9 methylation-dependent in placental trophoblasts, which further suggest that oxidative stress and aberrant histone modification have significant impact on placental trophoblasts/fetal programming in preeclampsia.